Angola : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper assesses macroeconomic fiscal risks and the benefits of improved fiscal risk management in Angola. Angola faces fiscal risks coming from multiple sources, such as volatility in oil prices and production, macroeconomic shocks, weak macroeconomic forecasting; weaknesses in public fiscal management, energy subsidies, potential delays of oil revenue transfers from the state-owned oil company Sonangol to the Treasury, and contingent liabilities from state-owned banks and enterprises. Addressing these risks requires action in various fronts, including more transparent fiscal reporting, improved forecasting of fiscal aggregates and other macroeconomic variables, developing a fiscal stabilization fund with more flexible deposit and withdrawal rules, strengthened public expenditure controls, and more timely oil revenue transfers from Sonangol to the Treasury.